2018
DOI: 10.31454/usb.419833
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Financial Clarity and Environmental Quality in Turkish Economy: Empirical Application

Abstract: Öz Dünya çapında yaşanan küreselleşme süreci ile birlikte dünya ülkeleri ticari ve finansal liberalizasyon uygulamalarına büyük önem vererek ekonomilerine hızlı bir ivme kazandırmışlardır. Bunun sonucu olarak son yıllarda çevre-ekonomi ilişkisinin varlığından bahsedilmektedir. Bu bağlamda, çalışmada Türkiye için 1970-2015 dönemini kapsayan yıllık veriler kullanılarak finansal dışa açıklık, ticari açıklık, kişi başına düşen gelir ve karbondioksit emilimi (CO2) değişkenleri arasındaki dinamik ilişkilerin varlığı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Mudam et al ( 2018) investigated the existence of dynamic relationships between financial openness, trade openness, per capita income and carbon dioxide emissions (CO 2 ) variables through VAR model by using annual data covering the period 1970-2015 for Türkiye. As a result of the analysis, it was revealed that 0.46% of the change in CO 2 emissions was explained by financial openness, 1.04% by per capita income and 0.42% by trade openness [35].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Mudam et al ( 2018) investigated the existence of dynamic relationships between financial openness, trade openness, per capita income and carbon dioxide emissions (CO 2 ) variables through VAR model by using annual data covering the period 1970-2015 for Türkiye. As a result of the analysis, it was revealed that 0.46% of the change in CO 2 emissions was explained by financial openness, 1.04% by per capita income and 0.42% by trade openness [35].…”
Section: Literature Reviewmentioning
confidence: 97%